A multilevel analysis of the double burden of malnutrition among under-five children within the same household in Indonesia - Agnes Boenardy; Fumihiko Yokota; Anak Agung Sagung Indriani Oka; Megan Chong Hueh Zan; Minh Anh Nguyen; Ahnav Bil Auvaq; Ahmad Putra Hadaetana; Intan Aziizah; Nurholis Majid (Universitas Gadjah Mada, 2026)
Purpose: Indonesia faces a persistent double burden of malnutrition (DBM), in which undernutrition and overnutrition coexist within populations. Although national stunting rates have declined, other nutritional challenges persist across provinces, with moderate-to-high rates indicating a complex nutritional transition. This study aims to identify individual, household, and contextual factors influencing the DBM among children in the same household and to provide evidence-based recommendations for region-specific, sustainable interventions. Methods: Using cross-sectional data from the Indonesian Nutrition Status Survey (SSGI) 2024, we analyzed 0-59-month-old children using multilevel logistic regression. Progressive models examined individual, household, and contextual (district or provincial) determinants of DBM, defined as the coexistence of undernutrition and overnutrition within households. Results: The prevalence of household-level DBM was 0.08%. In adjusted models, residing in Java–Bali was associated with significantly lower odds of DBM (OR = 0.39; 95% CI: 0.27–0.57). Children without birth certificates had significantly higher odds of experiencing DBM (OR=1.70; 95% CI: 1.48–1.95). Exclusive breastfeeding was associated with lower odds of DBM (OR = 0.54; 95% CI: 0.48–0.61). Households having more than one child under five showed substantially higher odds of DBM (OR = 3.30; 95% CI: 2.93–3.71), and district-level DBM remained a strong contextual predictor (OR = 2.01; 95% CI: 1.66–2.45). At the contextual level, the district-level DBM index remained strong contextual predictor. Conclusion: Household-level DBM among children in Indonesia exists but remains rare, yet it signals emerging intra-household nutritional inequalities and complexity. Key determinants include household structure, exclusive breastfeeding, birth certificate ownership, region disparities, and district-level contextual factors. These findings highlight the need for integrated, multilevel interventions that address both undernutrition and overnutrition, particularly in vulnerable households and underserved areas.